Good pharmacy practice assessment among community pharmacies in Lebanon - Danielle A. Badro; Hala Sacre; Souheil Hallit; Ali Amhaz; Pascale Salameh (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective: This study aims to assess good pharmacy practice (GPP) aspects and compare GPP scores among community pharmacies in Lebanon, using a tool developed jointly by the International Pharmaceutical Federation (FIP) and the World Health Organization (WHO) to improve and maintain standards of pharmacy practice. Methods: Data collection was carried out between July and October 2018 by a team of 10 licensed inspectors who work at the Lebanese Order of Pharmacists (OPL) and visited community pharmacies across Lebanon. The questionnaire was adapted to the Lebanese context and included 109 questions organized under five sections: socio-demographics, Indicator A (data management and data recording), Indicator B (services and health promotion), Indicator C (dispensing, preparation and administration of medicines), and Indicator D (storage and facilities). The value of 75% was considered as the cutoff point for adherence to indicators. Results: Out of 276 pharmacies visited, a total of 250 (90.58%) pharmacists participated in the study with one pharmacist being interviewed in every pharmacy. Results showed that 18.8% of pharmacists were generally adherents to GPP guidelines (scores above the 75% cutoff): 23.3% were adherent to indicator A, 21.6% to indicator B, 14.8% to indicator C and 13.2% to indicator D. Moreover, comparison of GPP scores across geographical regions revealed a higher adherence among community pharmacists working in the Beirut region compared to the North region, the South region, Mount Lebanon, and the Bekaa. Conclusions: Our study shows that community pharmacists in Lebanon do not fulfill GPP criteria set by FIP/WHO, and that this poor adherence is a trend across the country's geographical regions. Therefore, efforts should be made to raise awareness among pharmacists about the necessity to adhere to GPP guidelines and standards, and train them and support them appropriately to reach that goal. This is the first indicator-based comprehensive pilot assessment to evaluate GPP adherence in community pharmacies across Lebanon. Working on the optimization of this assessment tool is also warranted.